A Juridical Causality Relation between Political Dowry and Corruption by Regional Heads (Constitutional Law and Criminal Law Perspective) - Iriani, Dewi; Budiwati, Septarina; Inayah, Inayah; Safira, Martha Eri; Budiono, Arief; Izziyana, Wafda Vivid (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1163, 2020)
In early 2017 until February 2018, the Commission of Corruption Eradication arrested ten Regional Heads who redhandedly fired for political dowry and corruption. This research was sociological-juridical method with the aims of research to find the relation between political worry and corruption by regional heads. This research was also descriptive-analytic research with the subjections is descriptions on the constitutional and criminal law perspective. Cases handled by the Commission of Corruption Eradication are committing a crime, abusing the authority, making pledges to another party, accepting gifts and bribes from regional heads. Not only will the regional heads participate in the elections, but it also includes the family member of those regional heads. Corruption committed by the Regional Head from the Governor, Regent, and Mayor can be subjected to the element of criminal acts and violate Law No. 31 of 1999 Act No. 20 of 2001 concerning Eradication of Corruption Crimes.